Directed evolution of a plant Rubisco chaperone with altered client recognition - Siyu Li; ByungUk Lee; Yichong Lao; Sirawit Lertwiriyapiti; Xuhui Huang; Tina Wang (Proceedings of the National Academy of Sciences, 2025)
Improving the Calvin–Benson–Bassham cycle enzyme Ribulose 1,5-bisphosphate carboxylase/oxygenase (Rubisco) has the potential to increase crop productivity. However, the selectivity of the chaperones mediating Rubisco assembly in vascular plants toward their cognate Rubisco presents a substantive roadblock to both Rubisco protein engineering and transgenic expression of heterologous Rubisco orthologs, both of which necessitate changes to the Rubisco sequence. Here, we ask whether a plant Rubisco chaperone can be reprogrammed by directed evolution to accommodate a nonnative client. We developed a selection strategy to assess Rubisco assembly factor activity in high-throughput and used this selection to identify mutants of the chaperone Raf1 from Arabidopsis thaliana ( At Raf1) that assemble Nicotiana tabacum Rubisco, for which wild-type At Raf1 has minimal activity. We show that directed evolution can generate At Raf1 variants that enable significantly increased N. tabacum Rubisco assembly compared to wild-type At Raf1. Evaluation of evolved At Raf1s indicates that they retain the ability to assemble their native client and can assemble other dicot Rubisco orthologs that they were not evolved to recognize. This work may provide a strategy for addressing the constraints chaperone selectivity impose upon Rubisco-centric efforts to improve plant photosynthesis.